Sustainable Superabsorbent Polymer Synthesis from Pakhuri Leaves and Wheat Husk for Incontinence Pads - Jha, Sarb Narayan; Poudel, Sanjib; Kamar, Suman; Kamar, Suman; Kamar, Sujan; Shrestha, Smriti; Paudel, Bimala; Bastakoti, Narayan Datta; Gurung, Krishna; Gautam, Surendra Kumar; Yadav, Ram Jeewan (Journal of Nepal Chemical Society, 2026)
Carboxymethyl cellulose (CMC) was synthesized from Pakhuri (Ficus glaberrima Blume) and Wheat (Triticum aestivum L) husk, two abundant agro-forest wastes in Nepal, to develop sustainable superabsorbent polymer (SAP) precursors for incontinence pad and diapers applications. The synthesized CMC exhibited degrees of substitution (DS) in the range of 1–2, confirming successful etherification. However, CMC yields (40–65%) and swelling capacities (~200%) were relatively low compared to commercial SAPs. Characterizations (XRD, FTIR, and Brookfield’s viscosity measurement) revealed that Pakhuri has relatively superior SAP quality for incontinence pads and baby diapers since Pakhuri SAP is substitution efficient with low viscosity. However, substitution alone is insufficient to ensure high absorbency, with crosslink density, residual salts, and polymer morphology playing key roles in limiting water uptake. Despite these limitations, the study demonstrates the feasibility of converting underutilized biomass into functional SAP precursors. Future optimization of crosslinking, purification, and porosity enhancement is expected to significantly improve swelling performance, offering a pathway toward sustainable, low-cost SAPs suitable for hygiene and healthcare applications.